Komunikacyjne aspekty tworzenia wizerunku kraju, miasta i regionu - Daszkiewicz, Magdalena (Communicational Aspects of Building National, Regional and City Image, 2008)
Building a positive image is one of the ways of reaching competitive advantage. The paper addresses problems related to communicative aspects of image-building strategies of nations, cities and regions. The author presents areas and potential for building the image of territorial units based on intentional communicative activities.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 17, s. 63-70